Ventos de discórdia: território, energia eólica e conflitos socioambientais na zona costeira do Ceará - Silva, Débora Raquel Freitas da (2014)
The energy appears as essential for humanity input. With the historical development of society, especially since the advent of capitalist production, the demand for energy that gave strength to the mechanical machines became a priority. However, after the oil crisis began research in alternative energy since energy reserves from fossil fuels had advertised limits that come to an end in a few years. It is in this context that the wind arises. In Brazil, and particularly in the Northeast, we have seen a significant potential for the development of this technology, and the Brazilian government, facilitated its implementation. The overall objective of the research was to analyze these socio-spatial transformations and environmental conflicts in communities and Espraiado Volta River, located in the coastal zone of Ceará, with the critical point, the production of wind energy in Acaraú. These communities have experienced and responded differently to the arrival of the way and wind farms is about how this process occurred that this research focused. The research also focused on analyzing the ways of expansion of wind energy production in the Northeast, especially in Ceará, taking into account existing public policies for the sector in Brazil. In the way of research, as the field works were being hired, the search was adjusting to being carved as the theory is revealed in praxis and vice versa. To conduct the study we reviewed the literature on relevant concepts and research topics as well as a brief survey of a database that showed the expansion of wind farms in the state and its projected expansion. Subsequently, field surveys in selected communities where we conducted interviews and conversation wheels were made. It was found in several field social impacts arising from implementation of the wind farm Volta River, and also a process of resistance from the community Espraiado upon environmental licensing of wind farm Macaws. Although considered clean, renewable energy, wind energy in Ceará, has been causing environmental degradation of coastal systems, and especially to traditional communities. Routinely, complaints about privatization of protected areas, restrictions on the right to come and go, threats against the community organization and its leaders are made. Thus, in addition to technical, ie, as the production of wind energy has been made, it is necessary to reflect the process of how energy itself has been seen and managed by the Brazilian State. The process of resistance can be seen as a key factor in coping with situations which are contrary to the guarantee of the right to land and territory of traditional communities in general. So is the strength of the cry, the expression of the right to say 'no' and hoping to be able to make heard that sea-fishing communities in Ceará comes and should question the arrival of wind farms, trying to understand to whom and for what this energy.